Digoxin, an Overlooked Agonist of RORγ/RORγT - Karaś, Kaja; Sałkowska, Anna; Sobalska-Kwapis, Marta; Walczak-Drzewiecka, Aurelia; Strapagiel, Dominik; Dastych, Jarosław; Bachorz, Rafał A.; Ratajewski, Marcin (Frontiers in Pharmacology, 2019)
Digoxin was one of the first identified RORγT receptor inverse agonists inhibiting the differentiation of Th17 cells. However, this compound exhibits inhibitory activity at relatively high concentrations that mediate cytotoxic effects. We previously identified several cardenolides that are structurally similar to digoxin that were able to induce RORγ/RORγT-dependent transcription. These observations encouraged us to reanalyze the effects of digoxin on RORγ/RORγT-dependent transcription at low, noncytotoxic concentrations. Digoxin induced RORγ/RORγT-dependent transcription in HepG2 and Th17 cells. Furthermore, analysis of the transcriptomes of Th17 cells cultured in the presence of digoxin revealed the induction of the expression of numerous Th17-specific genes, including IL17A/F, IL21, IL22, IL23R, CCR4 and CCR6. Thus, our study, which includes data obtained from intact cells, indicates that digoxin, similar to other cardenolides, is a potent RORγ/RORγT receptor activator and that its structure may serve as a starting point for the design of dedicated molecules that can be used in the development of adoptive cell therapy.